KONSEP SAKINAH MAWADDAH WA RAHMAH MENURUT M. QURAISH SHIHAB DAN RELEVANSINYA TERHADAP PENDIDIKAN ANAK DALAM KELUARGA - Anis Suryani; Kadi Kadi (MA'ALIM: Jurnal Pendidikan Islam, 2020)
Family has a very big contribution in children's education. Because the family is the first environment for children. Basically, children are born to bring fitrah to good beliefs, that's where the family plays a role, especially parents who focus on and strengthen children's beliefs through education. For this reason, if we want to shape children's education with good education, it must begin at the time of family formation. Because a good family will continue a good generation. A good family according to Islam is the one that is sure to be mawaddahwarahmah. The results of the study found that the concept of Sakinah MawaddahWaRahmah according to M. Quraish Shihab is relevant to children's education because families that use the concept of sakinah mawaddah warahmah are families who are able to form good education for their children. Based on the process of relations between family and children, both underlie the relationship with the feeling of love and love. As well as to form a quality education, it starts from forming a family that is sakinahmawaddahwarahmah. However, it is needed to study more about family concepts, with the aim of increasing and instilling child education starting with the family, because the family is the first institution to instill education in children.Keywords: Children education, concept of sakinah, concept of mawaddah, concept of rahmah, family education.